EFEKTIFITAS PROBLEM BASED LEARNING MENGGUNAKAN MEDIA SMARTPHONE DITINJAU DARI KEMAMPUAN KOGNITIF SISWA - Loviga Denny Pratama; Minggar Putra Dea Ramadhan (UNZAH Genggong, 2021)
Currently, a technology media is needed in a mathematics learning process. However, some technological media such as smartphones are still not used optimally in creating a certain learning method in learning mathematics. This study aims to test the effectiveness of the Problem Based Learning (PBL) learning method facilitated by smartphone media by utilizing students' cognitive abilities. This study uses a quantitative approach (pretest-posttest with nonequivalent group design) with two treatments, namely the experimental class using the PBL method using Smartphone media and the control class using the Conventional PBL method. The subjects of this study were class VIII students who collected 63 students in the control class and 60 students in the experimental class. The effectiveness of the treatment in both classes was analyzed using the one sample t-test with a significance level of 5%. The data from this study were analyzed using independent sample t-test with a significance level of 5%. The results of this study indicate that PBL using smartphone media is more effective than conventional PBL. Based on the results of this study, a new variation of the Problem Based Learning (PBL) method was found, namely this method can be done through face-to-face learning or online learning.Keywords: Problem Based Learning, smartphone, insturctional media